An Efficient And Dynamic Encryption Model For Safeguarding Medical Cloud Storage Data - Selvam L, Arokia Renjit J (International Journal of Advanced Science and Technology, 2020)
Bio-Medical Healthcare field plays the one of the major parts for the application in cloud computing. Patients are allowed to upload their medical status in the cloud server. Only the privileged doctors are provided with authority to ingress the reports of the patient due to high sensitivity. Encrypting the information is done before uploading it in the cloud. In this technique, the patient generates an encryption key to the privileged doctor. The major disadvantage of this method is that, it is very complex to search over the encrypted data. Initially, we leverage Attribute based encryption technique to achieve two main securities characteristics, which is regarded as the most challenging domains of dynamic searchable symmetric encryption. To solve the dilemma in key sharing, the kNN based searchable encryption scheme is planned. The most important differentiation between the existing and the proposed format is that, the proposed format in storage, searching and updating complexity, the competence in the advancement of the scheme lays on the query generation based on the demonstration of the experiments.